THE INFLUENCE OF PARENTAL STYLES ON CHILD DEVELOPMENT: A LONGITUDINAL STUDY - Shah, Ahmed; Zainal, Ahmad; Hamdan, Salma (Yayasan Adra Karima Hubbi, 2026)
Parental styles play a significant role in shaping the development of children, influencing various aspects of their emotional, cognitive, and social growth. While much research has explored the immediate effects of parenting on children, few studies have examined these effects over an extended period. Understanding how different parental styles impact child development across time is essential for identifying long-term outcomes and informing parenting strategies. This study aims to investigate the long-term influence of different parental styles on child development, focusing on emotional regulation, social competence, and academic achievement. The goal is to explore how these parenting styles affect children at various developmental stages. A longitudinal design was employed, with data collected from 200 families over a span of 10 years. Parenting styles were categorized based on the authoritative, authoritarian, permissive, and uninvolved frameworks. Child development was measured using standardized assessments for emotional regulation, social competence, and academic performance. The findings revealed that children of authoritative parents showed higher levels of emotional regulation, better social skills, and stronger academic performance compared to children of authoritarian, permissive, or uninvolved parents. This study underscores the importance of authoritative parenting in fostering positive long-term outcomes in child development.